ENGLISH LANGUAGE TEACHING IN ISLAMIC EDUCATION IN INDONESIA; CHALLENGES AND OPPORTUNITIES - Tuti Hidayati (Englisia: Journal of Language, Education, and Humanities, 2016)
The dominant use of English in every field covering politic, economic, and sosial culture these days has manifested in its gaining a special position in many countries where it is not spoken. In Indonesia, it is a foreign language officially constituted as part of national education curriculum and becomes a requirement in a number of higher education and workforce entry. Yet, ELT in Indonesia faces various constraints including, but is not limited, the anxiousness to threat the purity of Bahasa Indonesia, the national language, and the worry about liberal western values embedded in English to corrupt the youngsters moral and attitudes. Interestingly, Islamic education that maintains a vital role among Indonesians has included English alongside other secular sciences and technology as part of its curriculum in its current advancement. In this regard, the paper will show how critical Islamic education role among Indonesians is, how ELT in Indonesia has developed, what challenges it experiences, and what opportunities it posseses in the context of Indonesian Islamic Education. The paper argues that Islamic education remains the choice of the Indonesian Muslim communities as long as it is able to meet the demands of living in the globalization era while keeping the Islamic values in all the learning process. It further suggests that ELT in Indonesia needs to incorporate Islamic values and show that English learning put no threats and negative influences to Indonesian culture in general and Islamic religious values in particular.